Strategies for marine pollution monitoring - Goldberg, Edward D. (New York : John Wiley & Son, Inc., 1976)
This volume has its origin in a report, Marine Pollution monitoring, which evolved from a workshop held at the santa catalina marine biological laboratory.
Part One. Methods of analysis-organic species -- Part Two. Methods of analysis-inorganic species -- Part Three. Methods of analysis - analytical aids -- Part Four. Sampling sites.
Includes bibliographical references and index.
Keywords: SEA-WATER -- ANALYSIS